Genetic variations in the gene encoding TFAP2B are associated with type 2 diabetes mellitus. - Maeda, S; Tsukada, S; Kanazawa, A; Sekine, A; Tsunoda, T; Koya, D; Maegawa, H; Kashiwagi, A; Babazono, T; Matsuda, M; Tanaka, Y; Fujioka, T; et al. (2005)
To search a gene(s) conferring susceptibility to type 2 diabetes mellitus, we genotyped nearly 60,000 gene-based SNPs for Japanese patients and found evidence that the gene at chromosome 6p12 encoding transcription-factor-activating protein 2beta (TFAP2B) was a likely candidate in view of significant association of polymorphism in this gene with type 2 diabetes. Extensive analysis of this region identified that several variations within TFAP2B were significantly associated with type 2 diabetes [a variable number of tandem repeat locus: chi(2)=10.9, P=0.0009; odds ratio=1.57, 95% CI 1.20-2.06, intron 1+774 (G/T); chi(2)=11.6, P=0.0006; odds ratio=1.60, 95% CI 1.22-2.09, intron 1+2093 (A/C); chi(2)=12.2, P=0.0004; odds ratio=1.61, 95% CI 1.23-2.11]. The association of TFAP2B with type 2 diabetes was also observed in the UK population. These results suggest that TFAP2B might be a new candidate for conferring susceptibility to type 2 diabetes and contribute to the pathogenesis of type 2 diabetes.